(untitled) (Academicia Globe: Inderscience Research, 2022)
We conducted a comprehensive clinical and laboratory examination of 60 vaccinated patients, aged 18 to 70 years, with a confirmed diagnosis of "COVID-19 in vaccinated patients." We established the clinical diagnosis of patients on the basis of epidemiological anamnesis, clinical examination and laboratory results. The mean age of the patients was 50.3±2.83; males predominated by gender.